1983
DOI: 10.1136/bmj.287.6398.1024
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of medical treatment of active chronic otitis media.

Abstract: Controlled trial of medical treatment of active chronic otitis media Active chronic otitis media is a common condition affecting 0 6%,' of adults in the United Kingdom. Initial management is usually by general practitioners, who annually prescribe systemic and topical antibiotics on at least 178 000 and 73 000 occasions respectively (unpublished observations). Despite this there have been few studies of the efficacy of antibiotics,'-4 and no study has included a control group of untreated patients or of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Systemic antibiotics seem less effective than topical antibiotics for reducing persistent otorrhoea after one to two weeks in adults 36 – 41 . Oral antibiotics and topical antiseptics seem equally more effective than topical antiseptics alone for reducing persistent discharge after two to four weeks in adults 37 . It is unclear which systemic antibiotic is more effective for reducing persistent otorrhoea 42 , 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Systemic antibiotics seem less effective than topical antibiotics for reducing persistent otorrhoea after one to two weeks in adults 36 – 41 . Oral antibiotics and topical antiseptics seem equally more effective than topical antiseptics alone for reducing persistent discharge after two to four weeks in adults 37 . It is unclear which systemic antibiotic is more effective for reducing persistent otorrhoea 42 , 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite obvious concerns about using an ototoxic agent in ears, reported cases of hearing loss were rare 9 . Tong, Woo and van Hasselt 11 documented one case, and Kellerhals 12 conducted a questionnaire‐based survey amongst Swiss ENT surgeons reporting 15 cases of moderate–profound sensorineural hearing loss presumed associated with antibiotic eardrop use. He estimated the incidence to be 1/3000–1/1000.…”
mentioning
confidence: 99%
“…However, this is contrary to the conclusions in the actual trial 19 which concluded that none of boric acid solution, topical aminoglycoside and systemic antibiotics had any advantage over aural toilet alone. Browning, Picozzi, Calder and Sweeney 11 studied boric acid and iodine powder and found it ineffective in COM, but their study included mastoid cavities. Other antiseptic agents tried include zinc peroxide powder, iodine powder and dilute methylated spirit eardrops 20 .…”
mentioning
confidence: 99%
“…There are no RCTs comparing topical antiseptics versus placebo or no treatment. One RCT demonstrated no significant difference between topical antiseptics plus ear cleansing under microscopic control and either topical or oral antibiotics 7 . Another RCT found no significant difference in resolution of ear discharge between topical povidone–iodine and topical quinolone 8 .…”
Section: Efficacy Of Topical Aminoglycosides In the Treatment Of Csommentioning
confidence: 99%